Multiple criteria analysis of a dwelling life cycle/Vienbučių gyvenamųjų namų gyvavimo proceso daugiakriterinė analizė - Kvederytė, Nerija; Zavadskas, Edmundas Kazimieras; Kaklauskas, Artūras (Journal of Civil Engineering and Management, 2000)
The determination of the utility degree and value of the project under investigation and establishment of the priority order for its implementation does not present much difficulty if the criteria numerical values and significances are obtained and the multiple criteria decision-making methods used. The results of the project comparative analysis are presented as a decision-making matrix where columns contain n alternative projects being considered, while all quantitative information pertaining to them is found in lines. Quantitative description of the project provides the information about various aspects of a building life cycle (ie economical, technical, technological, infrastructural, legislative, etc). Quantitative information is based on the criteria systems and subsystems, units of measure, values and initial significances as well as the data on an alternative project. In order to select the best project, it is necessary, having formed the decision-making matrix, to perform the multiple criteria analysis of the projects. This is done by comparing criteria numerical values and significances and analysing the conceptual information of the investigated project. One of the major tasks is to determine the significances of the criteria. This paper presents a new method for complex determination of the criteria significances taking into account their quantitative and qualitative characteristics. When performing multiple criteria assessment of projects it is necessary to normalise the criteria values describing the projects and then to weight them. This creates a possibility to compare the criteria values with different measuring units and to determine the most efficient alternatives. The significances of all criteria must be coordinated among themselves. The method of complex determination of significances allows to determine significances of criteria which are maximally interrelated and depend on qualitative and quantitative characteristics of all criteria. A method of multiple criteria complex proportional evaluation of the projects discussed in this paper assumes direct and proportional dependence of significance and priority of investigated versions on a system of criteria adequately describing the alternatives and on values and significances of the criteria. The system of criteria is determined and the values and initial significances of criteria are calculated by experts. All this information can be corrected by interested parties (customer, users, etc) taking into consideration their pursued goals and existing capabilities. The degree of utility Nj of a building life cycle is directly associated with quantitative and conceptual information related to it. A degree of dwelling life cycle utility reflects the extent to which the goals pursued by the interested parties are attained. The paper concludes with a demonstrative example, concerning the multiple criteria assessment of plot, dwelling, contractor and maintenance alternatives, and dwelling life cycle variants are being developed based on these alternatives of solutions.Article in Lithuanian.First Published Online: 26 Jul 2012